Cryptococcal neoformans profiles in peripheral blood neutrophils: An unusual presentation - Srinivas Upendra; Kar Rakhee; Saxena Renu; Prasad Pati (Wolters Kluwer Medknow Publications, 2008)
We report an unusual observation of Cryptococcal neoformans profiles engulfed by neutrophils on a routine peripheral blood smear examination in an HIV-negative young female patient who presented with perforation of large bowel following a pregnancy termination procedure by an untrained midwife.